2016
DOI: 10.1073/pnas.1601252113
|View full text |Cite
|
Sign up to set email alerts
|

Putative oncogene Brachyury ( T ) is essential to specify cell fate but dispensable for notochord progenitor proliferation and EMT

Abstract: The transcription factor Brachyury (T) gene is expressed throughout primary mesoderm (primitive streak and notochord) during early embryonic development and has been strongly implicated in the genesis of chordoma, a sarcoma of notochord cell origin. Additionally, T expression has been found in and proposed to play a role in promoting epithelial-mesenchymal transition (EMT) in various other types of human tumors. However, the role of T in normal mammalian notochord development and function is still not well-und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 39 publications
6
31
0
Order By: Relevance
“…However, in future experiments, it would be informative to carry out AX grafts in the Ptch1 reporter strain, and investigate levels of Ptch1 in these after culture to find out whether it is high in donor AX that is no longer associated with the streak. Finally, while many studies have implicated T in the EMT in various cell lines (e.g., (Hamilton et al, 2012), results of studies in vivo favor an essential role for T in specification of cell fate, and not the EMT or cell proliferation (Zhu et al, 2016). Our data accord with a general role for T in stem cell identity within the AX, where it is found with other stem cell factors.…”
Section: Discussionmentioning
confidence: 99%
“…However, in future experiments, it would be informative to carry out AX grafts in the Ptch1 reporter strain, and investigate levels of Ptch1 in these after culture to find out whether it is high in donor AX that is no longer associated with the streak. Finally, while many studies have implicated T in the EMT in various cell lines (e.g., (Hamilton et al, 2012), results of studies in vivo favor an essential role for T in specification of cell fate, and not the EMT or cell proliferation (Zhu et al, 2016). Our data accord with a general role for T in stem cell identity within the AX, where it is found with other stem cell factors.…”
Section: Discussionmentioning
confidence: 99%
“…The transcription factor Brachyury (T) is expressed in the developing notochord and is associated with maintaining a healthy immature NP phenotype and essential for normal spine formation. 28,29 Transfection of transcription factors have widely been established and documented for reprogramming studies, specifically turning somatic cells into induced pluripotent stem cells (iPSCs). 30 Thus, cellular reprogramming in this study refers to the transformation or reversal of a diseased cell back to its healthy (non-degenerate) phenotype.…”
mentioning
confidence: 99%
“… 14 Recent studies have shown that T‐Brachyury is expressed and functions in the notochord at E10.5. 15 Shh Cre inducible T‐Brachyury shRNA expressing T‐Brachyury knockdown mice show a phenotype with a costal level of vertebral malformation or loss because of the loss of the notochordal cells, which indicates that T‐Brachyury is essential for normal spine formation 15 . Even after the completion of the NP formation, T‐Brachyury is still strongly expressed in the NP cells, particularly in the notochordal cells.…”
Section: Transcription Factors Related To Np Developmentmentioning
confidence: 99%
“…T-Brachyury is a transcription factor that plays a critical role in embryonic mesoderm development, particularly for the formation of the notochord ( Figure 2A) (Table 1). 14…”
Section: The Structural Analysis and Developmental Program Of Ivdsmentioning
confidence: 99%